Educação de jovens e adultos: os desafios e dificuldades do ensino da EJA na escola São Miguel no município de Abaetetuba - SOUZA, Emília Cristina Caripuna de (2023)
This work, on the theme "Education of Young and Adults: the challenges and difficulties of teaching EJA" aims to analyze the challenges and difficulties existing in this type of education, aiming to understand this educational context that covers people of different age groups. with numerous barriers that make it difficult to return to the school environment and the acquisition of an effective literacy process. It was formulated as research questions to be investigated: what are the challenges and difficulties faced by EJA teachers and students? How is the teaching of EJA in São Miguel school, in its methodological aspects? Is the reality of the students being taken into account in the construction of the curriculum? As a reference, the study of official normative documents and Paulo Freire's theories on youth and adult education was used. The methodology used was of the Qualitative Research type and the techniques for data colleagues were participant observation and semi-structured interviews. As a result, this study shows how relevant Youth and Adult Education is for the achievement of student autonomy and also for their social life in addition to their training. Analyzing this study, it is right to say that Young and Adult Education came from a long trajectory with many obstacles that hampered its effectiveness for some time, but that from the moment it was established in the legislation, there was an advance in relation to the policies educational programs for Young and Adult Education.